PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING UNTUK MELATIH BERPIKIR KREATIF SISWA MI DALAM PEMBELAJARAN IPA MATERI GLOBAL WARMING - Kiky Chandra Silvia Anggraini; Elda Fitria Ningsih; Mega Syagita (Universitas Islam Lamongan, 2018)
This study aims to determine the effect of guided inquiry learning model to improve the critical thinking of MI Global Warning students in SD Tlogoanyar lamongan. The method is carried out by conducting pre-experiment by conducting a pretest and posttest during the research. The instruments used in the form of written tests and for data analysis using paired sample t test with the help of SPSS 25. based on the pretest posttest value done by students get the maximum value of 100 for the posttest while the drinking value is 80. After the paired test sample t test is known if the significance value equal to 0.00 or smaller than 0.005. which means Ha was accepted and Ho rejected.